CONTRIBUTIONS SENT TO THE IASB/FASB CONCERNING THE REVISION OF THE DRAFT REVENUE RECOGNITION - Tavares, Márcia Ferreira Neves; Anjos, Luiz Carlos Marques dos; Paulo, Edilson (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
This study aimed to investigate how the influencers incentives of companies‟ contributions sent to the IASB / FASB, concerning the Revised Exposure Draft revenue recognition, are related to theories of regulation already developed within the theory of accounting. The research was conducted through content analysis, in which demands were identified within the said draft. The arguments that promoted the expression of different interest groups were analyze. It was used a sample of 30 private companies, representatives of the most active geographic regions in the world. The results demonstrated that there is a relation between the incentives of firms and the theory of competition among interest groups. In addition, there are also strong complaints by firms about the excess of information required by regulators, finding support in the theoretical concept of over production. Many of the arguments made by companies occur because the regulators do not provide a specific accounting theory underlying the proposed operational procedure.